Ergogenic Benefits of β‐Hydroxy‐β‐Methyl Butyrate (HMB) Supplementation on Body Composition and Muscle Strength: An Umbrella Review of Meta‐Analyses - Mohammad Vesal Bideshki; Mehrdad Behzadi; Mehrdad Jamali; Parsa Jamilian; Meysam Zarezadeh; Bahram Pourghassem Gargari (Journal of Cachexia, Sarcopenia and Muscle, 2025)
ABSTRACT Background β‐Hydroxy‐β‐methyl butyrate (HMB) is a metabolite of the amino acid leucine, known for its ergogenic effects on body composition and strength. Despite these benefits, the magnitude of these effects remains unclear due to variability among studies. This umbrella review aims to synthesize meta‐analyses investigating the effects of HMB on body composition and muscle strength in adults. Methods A comprehensive literature search was conducted in Scopus, PubMed and Web of Science without date or language restrictions until August 2024. The study protocol was registered at Prospero (No. CRD42023402740). Included studies evaluated the effects of HMB supplementation on body mass, fat mass (FM), fat‐free mass (FFM), muscle mass and performance outcomes. Effect sizes (ESs) and 95% confidence intervals (CIs) were calculated, and a random‐effects model was used for meta‐analysis. Standard methods assessed heterogeneity, sensitivity and publication bias. The methodological quality of included studies was assessed using the AMSTAR2 tool. Results Eleven studies comprising 41 data sets were included, with participants aged 23–79 years. HMB supplementation significantly increased muscle mass (ES: 0.21; 95% CI: 0.06–0.35; p = 0.004), muscle strength index (ES: 0.27; 95% CI: 0.19–0.35; p < 0.001) and FFM (ES: 0.22; 95% CI: 0.11–0.34; p < 0.001). No significant changes were observed in FM (ES: 0.03; 95% CI: −0.04 to 0.35; p = 0.09) or body mass (ES: 0.09; 95% CI: −0.06 to 0.24; p = 0.22). The quality assessment revealed that five studies were of high quality, three were of low quality and three were of critically low quality. Conclusions HMB supplementation may benefit individuals experiencing muscular atrophy due to physiological conditions, particularly enhancing muscle mass and strength without significant changes in fat mass or body weight.